2016
DOI: 10.1016/j.jascer.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and size control of monodispersed BaTiO3–PVP nanoparticles

Abstract: Monodispersed, spherical nanoparticles of the BaTiO 3-polyvinylpyrrolidone (BT-PVP) composite were synthesized through the surface modification of the oxide BT by the polymer PVP, using TiCl 4 , BaCl 2 , PVP, and KOH (as the mineralizer) in an aqueous solution. To reduce the size of the particles and ensure that they were monodispersed, the concentrations of the Ba and Ti sources were increased and the reaction parameters such as reaction temperature, reaction time, and KOH concentration were optimized. As a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
4
20
0
Order By: Relevance
“…PVP is widely used as a stabilizer, which prevents nanoparticle aggregation via PVP steric effect. For the BT-PVP particles prepared at a relatively low temperature (80 • C) and atmospheric pressure in our previous study, no changes in the chemical structure of the PVP layer adsorbed on the BT surface via hydrogen bonding between the OH group of BT species and C O groups of PVP molecules were detected [15]. Izu et al [27] reported the PVP cross-linking observed on the surface of CeO 2 nanoparticles, which were prepared in ethylene glycol at a temperature of 190 • C and atmospheric pressure.…”
Section: Effect Of Reaction Temperature and Time On Dispersion Of Batmentioning
confidence: 67%
See 1 more Smart Citation
“…PVP is widely used as a stabilizer, which prevents nanoparticle aggregation via PVP steric effect. For the BT-PVP particles prepared at a relatively low temperature (80 • C) and atmospheric pressure in our previous study, no changes in the chemical structure of the PVP layer adsorbed on the BT surface via hydrogen bonding between the OH group of BT species and C O groups of PVP molecules were detected [15]. Izu et al [27] reported the PVP cross-linking observed on the surface of CeO 2 nanoparticles, which were prepared in ethylene glycol at a temperature of 190 • C and atmospheric pressure.…”
Section: Effect Of Reaction Temperature and Time On Dispersion Of Batmentioning
confidence: 67%
“…Very few research studies about polyvinypyrrolidone (PVP) was utilized as a dispersant for BT nanoparticles, although PVP has been widely used in the synthesis of metal and other metal oxide nanoparticles as a stabilizer, template, and inhibitor of particle growth. In a previous study, we have reported the synthesis of highly disperse BT-PVP nanoparticles at temperature below 100 • C and atmospheric pressure that PVP served as a stabilizer and inhibitor [14], through adsorbed on the BT surface via hydrogen bonding [15]. The dispersion of the synthesized nanoparticles was achieved via the PVP steric effect; however, the phase of the BT-PVP obtained at low temperatures was cubic.…”
Section: Introductionmentioning
confidence: 99%
“…This induces defects in the thin films and imparts an uneven surface, and the nanoparticles cannot exhibit their inherent characteristics, which reduces the performance of the electrical components. In order to solve this problem, highly dispersible BT nanoparticles were prepared with polyvinylpyrrolidone (PVP) by the low temperatures synthesis (LTS) and hydrothermal (HT) process, referred to as LBT-PVP and HBT-PVP respectively, as reported in our previous paper [ 21 , 22 ]. The nanoparticles prepared by these methods can be dispersed as suspension in a coating slurry, and with these particles thin film layers can be prepared easily and quickly by a bar coating process as Itoh et al reported [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The method, which succeeded in solving the problem of a fine particle size and dispersion in one step, was motivated by the core-shell particle process proposed by Izu et al [ 15 ]. Other authors attempting to obtain smaller high-dispersion nanoparticles prepared highly dispersed 80-nm-sized cubic BT-PVP particles by controlling the reaction parameters and the metal ion concentration in solution [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two well-known approaches were proposed in the form of an in-situ reaction and dissolution-precipitation reaction for the growth of BT in a hydrothermal process [ 16 ]. To understand which one prevails and which one leads to high-quality BT, the use of various sources of Ti and the ratio of Ti to Ba were studied, with TiO 2 frequently used as the source of Ti raw material [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%